UNRAVELLING THAI EFL UNDERGRADUATE STUDENTS’ MOTIVATION-ENGAGEMENT PROFILES IN ACADEMIC WRITING ALONG WITH THEIR CHALLENGES - Averina, Fidelis Elleny; Kanasya, Alfonsa Vina (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
Carrying out academic tasks requires some skills, one of which is writing. In countries where English is regarded as a foreign language, it can be particularly challenging for the students to master this skill since they are EFL beginning learners who are still developing. This requires students to possess good motivation-engagement which can help them to accomplish the demanded tasks. Derived from the rationale, this research aimed to unravel Thai EFL Undergraduate students’ motivation-engagement profiles Academic Writing and the challenges. These challenges they encountered might negatively impede their motivation-engagement. This descriptive qualitative research utilized a Likert-scale questionnaire and one section of open-ended questions that were distributed to sixty-eight Xavier Learning Community (XLC) students in Chiang Rai, Thailand. The findings showed that adaptive cognition became the most dominant motivation-engagement profile followed by adaptive behavior, impending cognition, and maladaptive behavior. In addition, it was revealed that the students in XLC showed a good motivation-engagement profile in Academic Writing despite the challenges that they encountered. These challenges include language use, paraphrasing, coherence, and cohesion. The result of this research is beneficial for educators and writing teachers, especially in designing instructions to sustain students’ motivation-engagement profiles.